2016
DOI: 10.1016/j.eats.2016.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic All-Inside Posterior Cruciate Ligament Reconstruction: Overcoming the “Killer Turn”

Abstract: One of the most challenging arthroscopic surgical procedures is posterior cruciate ligament (PCL) reconstruction. PCL injuries account for 20% of all knee ligamenterelated injuries. These may be isolated or occur as part of poly-ligament injuries. With the possibility of PCL reconstruction with the all-inside technique, there has been a surge in interest in treating PCL injuries. With the PCL being one of the strongest ligaments in the body and a primary restraint to posterior translation of the tibia, the nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…Another technical consideration when performing PCL reconstruction is managing the so-called “killer turn” at the proximal aperture of the tibial tunnel. 10 The “killer turn” causes difficulty with graft shuttling and has also been implicated in graft attenuation. 11 Our technique uses specific steps to mitigate both of these challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Another technical consideration when performing PCL reconstruction is managing the so-called “killer turn” at the proximal aperture of the tibial tunnel. 10 The “killer turn” causes difficulty with graft shuttling and has also been implicated in graft attenuation. 11 Our technique uses specific steps to mitigate both of these challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies revealed the optimal angle to place the tibial guide. 5,[27][28][29] Using a tibial aimer, the tunnels were made with an orientation of 50°to the tibial plateau with an external entry point approximately 1.5 cm medial to the tibial tubercle as previous study showed. 5 A guidewire (2.0-mm K-wire) was placed in the exit point of the PCL tibial tunnel (Figure 1).…”
Section: Tibial Tunnel Preparationmentioning
confidence: 99%
“…Tibial attachment of the PCL is located ∼1 cm distal to the joint surface, resulting in a sharp angle, where the graft for the tibial tunnel exists, commonly known as “killer turn”. 5 , 6 , 7 Another disadvantage is the requirement of creating additional arthroscopic approaches, including trans-septal portal, which can cause difficulties for inexperienced surgeons. The authors present a surgical technique for arthroscopic remnant preserving 3-portal PCL reconstruction, with opposite to commonly described graft passage direction, which overcomes difficulties associated with the killer turn.…”
Section: Introductionmentioning
confidence: 99%